PELATIHAN UNTUK PELATIH (TRAINING FOR TRAINER) MANAJEMEN ORGANISASI INTRA SEKOLAH BAGI PENGURUS OSIS SE-KKM MAN 1 METRO LAMPUNG TIMUR - Triatmojo, Fery; Atika, Dewi Brima; Meutia, Intan Fitri (Prosiding Pengabdian FISIP Unila, 2012)
In an effort to achieve organizational goals, activists intra-school organizations need to be provided adequate ability and skills in the management of the organization. Management is important because it is bases of all the planning activit ies of an organization, including organizational units. In Management, an organization identified in the present circumstances, direction or goal to be achieved, how to achieve goals, and with whom, and for what they are working. Training of Trainers to Intra-School organizations (OSIS Se-KKM MAN 1 Metro East Lampung) was held on Wednesday, July 18, 2012, at the campus MAN 1 Metro, East Lampung. A total of 35 student became a trainee. Training of Trainers Intra-school Organizational (OSIS Se-KKM MAN 1 Metro East Lampung) has been successful in increasing the understanding and skills of the participants related to organizational management. Improved understanding and skills of the average participant was 20.5%. Initial understanding of participants before the training was given by 69.4%, and after training, there is increased understanding of the end to be 89.9%. Activity Plan for follow-up should get the support and training of further guidance from Pembina organization, Vice of Head Master and mentor otherÂ teachers, so that the various materials that have been granted are expected to be followed by each intra-school organizational.Â Â Keywords: organizational management, intra-school organizational